Glutamatergic Regulation of miRNA‐Containing Intraluminal Vesicle Trafficking and Extracellular Vesicle Secretion From Cortical Neurons - Marcela Bertolio; Qiyi Li; Francesca E. Mowry; Kathryn E. Reynolds; Rashed Alananzeh; Haichao Wei; Kyoeun Keum; Rachel Jarvis; Jiaqian Wu; Yongjie Yang (Journal of Extracellular Vesicles, 2025)
ABSTRACT Neuronal extracellular vesicles (microvesicles and exosomes) are emerging secreted vesicular signals that play important roles in the CNS. Currently, little is known about how glutamatergic signalling affects the subcellular localisation of exosome precursor intraluminal vesicles (ILVs), microRNA (miR) packaging into ILVs and in vivo spreading of neuronal EVs. By selectively labelling ILVs and exosomes (but not plasma membrane‐derived MVs) with GFP‐tagged human CD63 (hCD63‐GFP) in cortical neurons, we found that glutamate stimulation significantly redistributes subcellular localisation of hCD63‐GFP+ ILVs, especially decreasing its co‐localisation with multi‐vesicular body (MVB) marker Rab7 while substantially promoting EV secretion. Interestingly, glutamate stimulation only modestly alters EV miR profiles based on small RNA sequencing. Subsequent in vivo cortical neuronal DREADD activation leads to significantly more widespread hCD63‐GFP+ area in hCD63‐GFPf/+ mice, consistently supporting the stimulatory effect of glutamatergic activation on neuronal EV secretion and spreading. Moreover, in situ localisation of hCD63‐GFP+ ILVs and hCD63‐GFP+ secreted exosomes from specialised HB9+ and DAT+ neurons were also illustrated in the CNS. Taken together, our results demonstrated that glutamate activity stimulates neuronal exosome secretion and spreading in vitro and in vivo, but only modestly affects miR cargo packaging in neuronal exosomes.